New Synonym and New Species Record of Filchneria (Plecoptera: Perlodidae) from China with a Morphological, Phylogenetic and Biogeographic Study on This Genus - Qing-Bo Huo; Bin-Qing Zhu; Abdur Rehman; Dávid Murányi; Yu-Zhou Du; Jun Wu (Insects, 2022)
The type species of Filchneria Klapálek, 1908, F. mongolica (Klapálek, 1901), is based on a single female collected from Mongolia, but it was considered the same as another species, F. songi from Qinling, China, when the genus Filchneria was proposed. This study narrates the story of these two species, which have been confused for a century. Until now, the distribution of F. mongolica has been confirmed only in Mongolia and Russia, and we recently recorded it for the first time in Inner Mongolia as a new species record in China. Additionally, the genus Sinoperlodes is a junior synonym of Filchneria, as demonstrated by both the morphological and molecular analysis. Phylogenetic analysis based on the subfamily Perlodinae is provided, along with morphological and biogeographic comparisons of Filchneria and its relatives.